PENGHIMPUNAN PENDAPATAN NGEFANS SAWERAN : MISTIK SEMAR MESEM PENYANYI DANGDUT (Studi pada Penyanyi Orkestra Melayu New Kendedes) - Prasetyo, Whedy (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2020)
This study aims to examine the activities of dangdut singers to collect their entertainment income.Activities by basing on mystical routines for semar mesem.The use of this mystic is in recognition of the singer's income. Recognition in the form of collection throughsaweran mechanism. The mechanism angefans saweran contribution is findings of this study. Qualitative methods with an ethnometodology approach was used in this study. The results revealed the mystical semar mesemthat was used as a "tali pengasihan" by the singer made a spectator ngefans. Saweran's contribution as his goal, why is that? Because saweranas a unit of income calculation allows the singer to "hope" to fulfill his wishes. The use of money "manggung on air" has made it easier for singers to express their performances and also the songs they perform. This achievement gives the spirit of additional income obtained to be more in a relationship to continue the gig is measured and reliable.